Electrocatalytic reactions mediated by N,N,N',N'-Tetraalkyl-1,4-phenylenediamine redox liquid microdroplet-modified electrodes: chemical and photochemical reactions In, and At the surface of, femtoliter droplets. - Wadhawan, J; Wain, A; Kirkham, A; Walton, D; Wood, B; France, R; Bull, S; Compton, R (2003)
The electro-oxidation of electrolytically unsupported ensembles of N,N-diethyl-N',N'-dialkyl-para-phenylenediamine (DEDRPD, R = n-butyl, n-hexyl, and n-heptyl) redox liquid femtoliter volume droplets immobilized on a basal plane pyrolytic graphite electrode is reported in the presence of aqueous electrolytes. Electron transfer at these redox liquid modified electrodes is initiated at the microdroplet-electrode-electrolyte three-phase boundary. Dependent on both the lipophilicity of the redox oil and that of the aqueous electrolyte, ion uptake into or expulsion from the organic deposits is induced electrolytically. In the case of hydrophobic electrolytes, redox-active ionic liquids are synthesized, which are shown to catalyze the oxidation of l-ascorbic acid over the surface of the droplets. In contrast, the photoelectrochemical reduction of the anaesthetic reagent halothane proceeds within the droplet deposits and is mediated by the ionic liquid precursor (the DEDRPD oil).